German socialism - Finlay, T.A. (Statistical and Social Inquiry Society of Ireland, 1890)
The progress of that movement which we know by the somewhat ill-defined term, Socialism, is the most interesting, as it is the most important phenomenon of our present economic and social condition. During the past half century it has been taking more distinct shape and gathering ever increasing strength and volume. It has come to be a power with which the rulers of civilised nations?the representatives of the existing social order?must everywhere count, in reference to which they must frame a policy, which they must set themselves either to conciliate or to crush. I date the socialistic movement which at present agitates civilised society no further back than the year 1840.
Read Tuesday, 10th June, 1890
Keywords: Germany; Socialism; 314.15